A best practice framework for applying physiologically‐based pharmacokinetic modeling to pediatric drug development. (20th July 2021) - Johnson, Trevor N.; Small, Ben G.; Berglund, Eva Gil; Rowland Yeo, Karen
Abstract : Pediatric physiologically‐based pharmacokinetic (PBPK) models have broad application in the drug development process and are being used not only to project doses for clinical trials but increasingly to replace clinical studies. However, the approach has yet to become fully integrated in regulatory submissions. Emerging data support an expanded integration of the PBPK model informed approach in regulatory guidance on pediatrics. Best practice standards are presented for further development through interaction among regulators, industry, and model providers.